PERSEPSI KONSUMEN MILENIAL TERHADAP KUALITAS LAYANAN PASAR TRADISIONAL (STUDI KASUS PASAR TRADISIONAL DI WILAYAH D.I. YOGYAKARTA) - Elisabet Dita Septiari; Nadia Nila Sari (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2018)
It has been known that Millenial consumer acknowledged as productive and potential consumer. Their unique characteristic has become an attaractive target market for business especially retailer such as traditional market and modern market retailers. The intense competition from the emergence of modern market retailers giving a contribution on the declining number of tradisional market retailer. The problem such as unwell displaying issues, wet environment, uncomfortable, dirty,and interaction issues with the merchants and staffs in Yogyakarta’s tradisional market, has become a research focus of this paper. An overview about Service Quality has raised in order to gain perspective of Millenial consumer over traditional market. The result of this research shown that interaction quality need to be improve due to no standard communication applied between untrained merchants with the consumer. Physical environment quality and process quality need to get further attention by the tradition market administrator to serve Millenial consumer.